Magot Flour Performance in Increases Formula Feed Efficiency and Growth of Nirwana Race Tilapia (Oreochromis sp.) - Vini Taru Febriani Prajayati; Otie Dylan Subhakti Hasan; Mugi Mulyono (Universitas Gadjah Mada, 2020)
Tilapia is an economically important fish and is widely cultivated in Indonesia. More food in tilapia farming uses fish meal which needs to be replaced because of dependence as an imported product that affects production costs. One of the local raw materials that can be used as a source of animal protein is magot. This study aims to analyze the right proportion of magot flour with a combination of fish meal and magot flour in feed so as to produce maximum growth and feed efficiency for tilapia seeds. This research was conducted in September to December 2019. Test fish used were tilapia seeds measuring 1-2 cm with an average weight of 0.16 g with a stocking density of 1 fish / m3. Fish are fed twice a day with a percentage of daily feeding of 3% of fish biomass. This study used a completely randomized design (CRD) with five treatments and three replications. The treatment in this research is, treatment A = substitution of fish meal 100% with magot flour 0%, B = substitution of fish meal 75% with magot flour 25%, C = substitution of fish meal 50% with magot flour 50%, D = substitution of flour fish 25% with 75% magot flour, E = substitution of 0% fish flour with 100% magot flour. Data were analyzed using analysis of variance (ANOVA) if there were significantly different treatment effects followed by Duncan's Multiple Range Test with a significance level of 0.05. The results showed that the addition of magot flour 50% gave a significant result (P <0.05) on protein retention with a value of 14.83%, a specific growth rate with a value of 2.00%, absolute weight growth with a value of 4.34 g, and efficiency of utilization feed with a value of 93.59%. No effects were found in the the feed consumption rate and fish survival. Treatment C combination of 50% fish meal and magot flour can give the best results for the growth of Nirwana race Tilapia.